Characteristics of Sudden Commencements Observed by Van Allen Probes in the Inner Magnetosphere. Issue 2 (23rd February 2018) - Fathy, A.; Kim, K.‐H.; Park, J.‐S.; Jin, H.; Kletzing, C.; Wygant, J. R.; Ghamry, E.
Abstract: We have statistically studied sudden commencement (SC) by using the data acquired from Van Allen Probes (VAP) in the inner magnetosphere ( L = 3.0–6.5) and GOES spacecraft at geosynchronous orbit ( L =∼ 6.7) from October 2012 to September 2017. During the time period, we identified 85 SCs in the inner magnetosphere and 90 SCs at geosynchronous orbit. Statistical results of the SC events reveal the following characteristics. (1) There is strong seasonal dependence of the geosynchronous SC amplitude in the radial B V component at all local times. However, B V shows weak seasonal variation on the dayside in the inner magnetosphere. (2) The local time dependence of the SC amplitude in the compressional B H component at geosynchronous orbit is similar to that in the inner magnetosphere. (3) In a nightside region of L = 5.0–6.5, ∼19% of B H events are negative, while ∼58% of B H events are negative at geosynchronous orbit. (4) The amplitude of the SC‐associated E y perturbations varies systematically with local time with a morning‐afternoon asymmetry near noon. These observations can be explained by spatial and/or temporal changes in the magnetopause and cross‐tail currents, which are caused by changes in the solar wind dynamic pressure, with respect to spacecraft positions. Key Points: SC‐associated B field perturbations were observed in the inner magnetosphere by Van Allen Probes Weak seasonal variation of Δ B V was observed on the dayside in the inner magnetosphere The amplitude of SC‐associated E y perturbations varies systematically with local time